PARTISIPASI POLITIK BAGI PENYANDANG DISABILITAS PADA PEMILU SERENTAK TAHUN 2019 (Studi Kasus di Kabupaten Purwakarta) - Yuannita Kartika Hermana, - (2021)
Democratic elections are held if all citizens are guaranteed political rights.The problem of political participation is that there are members of the community with disabilities who are not fully able to carry out political participation properly.The research a qualitative approach with case studies in Purwakarta,data collection interviews,observation,documentation,data analysis by reduction,presentation, drawing conclusions.The results:1)The role of the KPU in political education,socialization of ballot paper use,coordination with disability organizations,2)Forms of political participation by persons with disabilities, namely giving voting rights,supporting one of the 2019 Election Candidates,participating in the campaign,3)The facilities provided by the KPU as needed, although in practice some obstacles occur. Keywords: Political Participation; Persons with Disabilities; Purwakarta Regency